A COMPARATIVE STUDY BETWEEN THE SIDE EFFECTS OF COPPER INTRAUTERINE DEVICE IN WOMEN WITH NON-SCARRED AND SCARRED UTERUS (Iraqi Journal of Medical Sciences, 2016)
Background:So many women think that the use of intrauterine devices in a scarred uterus carries high complications like increased uterine bleeding and pain and these side-effects may result in early removal of the device.Objective:The study was conducted to show the difference in the side effects of Copper intrauterine device (CuT380A) in women after vaginal deliveries and those with previous scar of cesarean section.Methods: The study group consisted of 411women who were using CuT380A device for contraception which has been fitted for more than 3months (240 of them had vaginal deliveries and 171 had one or more cesarean section scar). Complications of the CuT380A device were compared in both groups in regard to heavy vaginal bleeding (menorrhagia), painful menstrual cycles (dysmenorrhea), cycle irregularity, other types of pain (pelvic pain and backache) and infection. Both groups were further studied and complications were compared according to the duration of intrauterine device insertion.Results:The most common side-effects related to CuT380A were bleeding and pain. Menorrhagia was recorded in 35.42% and 29.24% while dysmenorrhea in 27.08% and 34.50% women of the non-scarred and scarred uterus groups respectively. These side effects were not statistically different between the two groups and they decreased significantly with time; menorrhagia decreased from 40.54% to 27.17% (P-value=0.035) and from 36.27% to 18.84% (P-value=0.014) while dysmenorrhea decreased from 31.76% to 19.57% (P-value=0.039) and from 41.18% to 24.64% (P-value=0.026) in non-scarred and scarred uterus groups.Conclusion:The study revealed that the side-effects of CuT380A device did not differ between non-scarred and scarred uterus and that menorrhagia and dysmenorrhea significantly decreased with time.Key words: CuT380A, non-scarred uterus, scarred uterus.
Keywords: CuT380A; nonscarred uterus; scarred uterus